2005
DOI: 10.1016/j.agwat.2004.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation application efficiency and deep drainage potential under surface irrigated cotton

Abstract: Furrow irrigation events conducted under usual farmer management were analysed to determine the irrigation application efficiencies being attained, and the magnitude of the irrigation contribution to deep drainage under surface irrigated cotton in Queensland. Application efficiencies were shown to vary widely from 17 to 100% and on average were a low 48%. Losses to deep drainage were substantial, averaging 42.5 mm per irrigation. This has the potential for significant environmental harm and also represents an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 8 publications
2
57
1
2
Order By: Relevance
“…Losses of up to 83 % of the water to deep drainage (including preferential and/or matrix flows) during furrow irrigation of cotton and sugar cane in vertisols were reported (Raine and Bakker, 1996;Dalton et al, 2001;Moss et al, 2001;Smith et al, 2005). Losses to deep drainage averaged 42.5 mm per irrigation (Smith et al, 2005), ranging from 50 to 300 mm yr −1 (Silburn and Montgomery, 2004 At the small-watershed scale (∼ 10 000 m 2 ), Pathak et al (2013) indicated that runoff from vertisols is smaller than runoff from sandier soils (alfisols) in an agricultural watershed near Hyderabad, India. The smaller runoff from the vertisols was attributed to preferential infiltration of local runoff into the soil cracks.…”
Section: Preferential Flow Of Water In Vertisols -Evidence From the Lmentioning
confidence: 99%
“…Losses of up to 83 % of the water to deep drainage (including preferential and/or matrix flows) during furrow irrigation of cotton and sugar cane in vertisols were reported (Raine and Bakker, 1996;Dalton et al, 2001;Moss et al, 2001;Smith et al, 2005). Losses to deep drainage averaged 42.5 mm per irrigation (Smith et al, 2005), ranging from 50 to 300 mm yr −1 (Silburn and Montgomery, 2004 At the small-watershed scale (∼ 10 000 m 2 ), Pathak et al (2013) indicated that runoff from vertisols is smaller than runoff from sandier soils (alfisols) in an agricultural watershed near Hyderabad, India. The smaller runoff from the vertisols was attributed to preferential infiltration of local runoff into the soil cracks.…”
Section: Preferential Flow Of Water In Vertisols -Evidence From the Lmentioning
confidence: 99%
“…These values were considered low when compared to potential values previously reported (Bos, 1980;Elliot & Walker, 1982;Solomon et al, 2007). Nevertheless, these AE values were similar or only slightly lower than those obtained under normal grower control as others have reported (Smith et al, 2005). These small values were partially justified by the small D req value due, in turn, to the shallow chufa plant root system (20 cm).…”
Section: Actual Irrigation Performancesmentioning
confidence: 56%
“…However, recent studies have shown that significant losses do in fact occur. For example, [19] evaluated surface irrigation events in cotton fields in Queensland and found that at the field level, irrigation application efficiencies varied widely from 17% -100% with an average of 48%. They also found that deep percolation losses averaged 42.5 mm per irrigation event, representing an annual loss of up to 2.5 ML/ha (250 mm).…”
Section: Seasonal Water Extraction From Each Soil Depthmentioning
confidence: 99%